Mediating and moderating effects of learned resourcefulness on depressive symptoms and positive ideation in hospital nurses in Taiwan - Chung, Chun-Chih; Lin, Mei-Feng; Ching, Yung-Chieh; Kao, Ching-Chiu; Chou, Yi-Ying; Ho, Ping-Hui; Chang, Hsiu-Ju (Research in nursing & health, 2012)
Learned resourcefulness (LR) is important in facilitating mental health in individuals experiencing depression, and positive ideation plays a further protective role in the prevention of suicidal ideation. The purpose of this study was to explore whether LR mediates or moderates the relationship between depressive symptoms and positive ideation in hospital nurses. Participants were 807 full‐time hospital nurses. The relationship between depressive symptoms and positive ideation was both mediated and moderated by LR after controlling for age, job title, and marital status. Continuing education and counseling strategies may increase nurses' LR and thereby enhance positive ideation and reduce risk of depression and suicide. © 2012 Wiley Periodicals, Inc. Res Nurs Health 35:576–588, 2012